Repeatability of Non–Contrast-Enhanced Lower-Extremity Angiography Using the Flow-Spoiled Fresh Blood Imaging. Issue 1 (January 2018) - Zhang, Yuyang; Xing, Zhen; She, Dejun; Huang, Nan; Cao, Dairong
Abstract : Purpose: The aim of this study was to prospectively evaluate the repeatability of non–contrast-enhanced lower-extremity magnetic resonance angiography using the flow-spoiled fresh blood imaging (FS-FBI). Methods: Forty-three healthy volunteers and 15 patients with lower-extremity arterial stenosis were recruited in this study and were examined by FS-FBI. Digital subtraction angiography was performed within a week after the FS-FBI in the patient group. Repeatability was assessed by the following parameters: grading of image quality, diameter and area of major arteries, and grading of stenosis of lower-extremity arteries. Two experienced radiologists blinded for patient data independently evaluated the FS-FBI and digital subtraction angiography images. Intraclass correlation coefficients (ICCs), sensitivity, and specificity were used for statistical analysis. Results: The grading of image quality of most data was satisfactory. The ICCs for the first and second measures were 0.792 and 0.884 in the femoral segment and 0.803 and 0.796 in the tibiofibular segment for healthy volunteer group, 0.873 and 1.000 in the femoral segment, and 0.737 and 0.737 in the tibiofibular segment for the patient group. Intraobserver and interobserver agreements on diameter and area of arteries were excellent, with ICCs mostly greater than 0.75 in the volunteer group. For stenosis grading analysis, intraobserver ICCs range from 0.784 to 0.862 and from 0.778 to 0.854, respectively. Flow-spoiled fresh blood imaging yielded a mean sensitivity and specificity to detect arterial stenosis or occlusion of 90% and 80% for femoral segment and 86.7% and 93.3% for tibiofibular segment at least. Conclusions: Lower-extremity angiography with FS-FBI is a reliable and reproducible screening tool for lower-extremity atherosclerotic disease, especially for patients with impaired renal function.